2007
DOI: 10.1097/01.nmc.0000298134.39785.6c
|View full text |Cite
|
Sign up to set email alerts
|

Kangaroo Care at Birth for Full Term Infants

Abstract: In this institution, birth kangaroo care was integrated into routine delivery room care, with nurses noting no change in nursing workload. Nurses have noted observing the crawling, latching, and successful breastfeeding of most infants. Because of the results of this pilot study, birth kangaroo care has been implemented successfully with all women who wish to participate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 15 publications
1
43
0
3
Order By: Relevance
“…Safarabadi Farahani et al Khadivzadeh et al and Karimi et al reported that SSC had a great positive effect on success rate of the first breastfeeding (100% vs 74%, 89.4% vs 2.2%, and 56.6% vs 35.6%, respectively) (30)(31)(32). These results were almost comparable with the results of studies by Moore et al and Walter et al (57,58). Basiri et al showed that frequency of feeding in the group receiving KMC for > 4 hours was higher than the frequency in the group receiving KMC for < 4 hours was (P < 0.05) (25).…”
Section: Breastfeedingsupporting
confidence: 88%
“…Safarabadi Farahani et al Khadivzadeh et al and Karimi et al reported that SSC had a great positive effect on success rate of the first breastfeeding (100% vs 74%, 89.4% vs 2.2%, and 56.6% vs 35.6%, respectively) (30)(31)(32). These results were almost comparable with the results of studies by Moore et al and Walter et al (57,58). Basiri et al showed that frequency of feeding in the group receiving KMC for > 4 hours was higher than the frequency in the group receiving KMC for < 4 hours was (P < 0.05) (25).…”
Section: Breastfeedingsupporting
confidence: 88%
“…They recognized that medical interventions affect mother-infant bonding and the initiation of breastfeeding when the mother does not feel well enough to care for her baby. Consequently, the fathers requested information about how cesarean surgery and other possible complications affect motherinfant bonding and breastfeeding and how fathers can support the clearly described mother-infant dyad (Moore, Anderson, & Bergman, 2007;Walters, Boggs, Ludington-Hoe, Price, & Morrison, 2007) while the mother and child are separated and after they are reunited. A plan for fathers to help if the mother is not able to care for her baby might support fathers having some feeling of control in a frightening situation.…”
Section: Discussionmentioning
confidence: 99%
“…[18,19] In addition: it regulates heartbeat, body temperature and breathing of the newborn; shortens interval between delivery, and initiation of breastfeeding; calms sleep; elongates breastfeeding period and enhances success of continued breastfeeding. [20,21] Public agencies, NGOs, UNICEF and WHO recommend that breast feeding should begin in the first hour after giving birth and advocate it as the only feeding method for the first 6 months of life. The American Academy of Pediatrics (AAP) has recommends that "healthy infants should be placed and remain in direct SSC with their mothers immediately after delivery until the first feeding is accomplished".…”
Section: Introductionmentioning
confidence: 99%